Aphidophagous coccinellids (insecta: coleoptera) in chili (capsicum annuum L.)ecosystems in Malaysia - Rahman , T; Mohamad Roff , M.N; Idris , A.B (Pusat Sistematik Serangga ,UKM, 2010)
The study was aimed to record and making a list of the aphidophagous coccinellids that preying on aphid, aphis gossypii glover (homoptera:aphididae)colonizing chili (capsicum annuum L) crop in Malaysia. The study was carried in chili fields at Mardi researsh stattion jalan kebun, Selangor, Malaysia from december 25, 2003 to february 29 2004. The A.gossypi infested chili plants were inspected by walking along the beds and adults of coccinellids seen were collected and brought back to laboratory for species indentification. A total of five coccinellids species were recorded namely the menochilus sexmaculatus fabricius, coelophora inaequialis (faricius) coccinella transversalis fabricius, harmonia occtomaculata (fabricius) and coelophora bissellatta (mulsant)(coleoptera: coccinellinae).Of these. M.sexmaculatus was the most abundant species colonizing chili followed by C.inaequialis, H.occtomaculata,and C.bissellatta. It is imperative to conduct further study on the impact of these spesies when alone or in combination as it has the potential to be on aphid population candidate for biological control agent of A.gossypii.